GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 209225 species occurrences available in GBIF matching the query: TaxonKey: Salmo trutta Linnaeus, 1758. The dataset includes 209225 records from 227 constituent datasets: 1959 records from Artdata. 1 records from MfN Fish Collection, Zoology. 96 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 26 records from Field Museum of Natural History (Zoology) Fish Collection. 396 records from NRM-Fishes. 6 records from Fish collection of National Museum of Nature and Science. 456 records from Øvre Heimdalsvatn, Radiocaesium (Cs-137) monitored annually in brown trout (Salmo trutta). 25 records from ArtenFinder. 1 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 2 records from CSIRO Ichthyology provider for OZCAM. 30 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 4 records from Queen Victoria Museum Art Gallery provider for OZCAM. 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 68 records from Museum Victoria provider for OZCAM. 67 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 1 records from Stausee (Oberdigisheim/Meßstetten). 794 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 11 records from Countryside Council for Wales - Lamprey Survey Data. 46 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 1 records from Schlern - (Bozen). 1 records from Schussenaue (Weingarten). 163 records from Fish specimens. 62 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 2 records from Fish Collection of Hokkaido University. 2 records from DINA. 100 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 12 records from UWFC Ichthyology Collection. 1 records from Natural History Museum Rotterdam (NL) - Chordata collection. 21444 records from Swedish Board of Fisheries (Fiskeriverket) - Swedish Electrofishing Registry. 10 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 1 records from European Molecular Biology Laboratory Australian Mirror. 48 records from BioFokus. 1 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 824 records from Inland Fisheries Ireland data on freshwater fish in Irish lakes. 1 records from Promberg1. 272 records from Swedish Board of Fisheries (Fiskeriverket) - Institute of Coastal Research. 1 records from Biodiversity records from Ireland - general. 4 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 10 records from Diveboard - Scuba diving citizen science observations. 48 records from UNSM Vertebrate Specimens. 1 records from Roter Berg Werdau (Leubnitz). 2 records from University of California Museum of Paleontology. 2 records from Merseyside BioBank - North Merseyside Fish (unverified). 35 records from University of Alberta Ichthyology Collection (UAMZ). 1 records from Neckartalsüdhang (Horb). 774 records from Monitoring data from the federal state Saxony (Germany). 18 records from FHSM Fish Collection. 277 records from Banc de dades de biodiversitat de Catalunya-VerteCat. 39 records from UF FLMNH Ichthyology. 135 records from Collection Pisces SMF. 1 records from Wanderweg am Windebyer Noor (bei Eckernförde). 100 records from Museum of Comparative Zoology, Harvard University. 3671 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_ICTIO. 1 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1 records from NSG Karwendel. 1 records from Kohlstattbrunnental. 16 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 1 records from Individual Sightings. 6 records from Plan de vertebrados de la Patagonia. 1 records from Spechtwald. 56 records from Ohio State University Fish Division (OSUM). 13406 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 18 records from LACM Vertebrate Collection. 1 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 9314 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 2 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 482 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 135 records from Museum of Zoology, University of Navarra. 15 records from Tulane University Museum of Natural History. 31 records from Geographically tagged INSDC sequences. 17 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 1472 records from Fishbase. 1 records from Reptiles, Amphibians and Fishes collection (ZA) in the Comparative Anatomy Collection of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Die Bachspezies 2008/2009. 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from UMZC Zoological Specimens. 1431 records from Inventario Español de Especies Terrestres (MAGRAMA). 5 records from Freshwater Fish Specimens of Lake Biwa Museum. 1 records from TNHC Ichthyology Collection. 1 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 208 records from NMNH occurrence DwC-A. 1 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 12 records from Database Schema for UC Davis Wildlife museum. 1 records from Knechtweide (Kohlfurth). 1 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 1 records from Lustadter Wald .. 1 records from Collection du Musée d'Histoire Naturelle de Nice. 1 records from Anymals+plants - Citizen Science Data. 5 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 230 records from Limnodata. 57 records from Ichthyology. 6 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 1 records from Olympiapark (München). 1066 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 1 records from Bay of Fundy Species List (OBIS Canada). 1 records from Stadtpark Schmölln. 1 records from Hamberger Brücke / Würmtal (Pforzheim). 1 records from Werremündung im Schwarzatal. 10 records from RBINS collections. 21 records from Canadian Museum of Nature - Fish Collection (OBIS Canada). 2 records from Colección de peces y macroinvertebrados del Museo de Historia Natural de la Pontificia Universidad Javeriana. 5 records from iziko South African Museum - Fish Collection (AfrOBIS). 15 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 9 records from SAIAB. 1 records from Gunma Museum of Natural History, Fish Specimen. 1 records from Unser Schulgelände. 3 records from Countryside Council for Wales - Shad Monitoring data. 339 records from Lund Museum of Zoology (MZLU). 1560 records from Biologiezentrum Linz. 170 records from Fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Ireland's BioBlitz 2012. 432 records from Biological and palaeontological collection and observation data MNHNL. 22 records from Collection Anatomie Histologie - SMF. 1 records from Fish Specimens of Museum of Tokushima Prefectural Museum, Japan. 4 records from Wetland Inventory (NV). 39 records from Zoology (Museum of Evolution - Uppsala). 301 records from Royal Dutch Angling Association (SVN) - Piscaria. 130 records from Fish collection, Natural History Museum, University of Oslo. 1 records from Collections ichtyologiques et herpétologiques (BOUM). 64 records from Australian Museum provider for OZCAM. 1 records from Zielbach (Töll). 30 records from Countryside Council for Wales - Bullhead Survey Data in Wales. 1 records from Stadtpark Sulzbach-Rosenberg. 2 records from IndOBIS, Indian Ocean Node of OBIS. 1 records from Freiburger Tag der Artenvielfalt. 239 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 1 records from Northern Territory Museum and Art Gallery provider for OZCAM. 16 records from MSUM Ichthyology and Herpetology Collections. 3 records from CSUC Vertebrate Collection. 100 records from Ichthyology Collection - Royal Ontario Museum. 1 records from Eppingen und Umgebung. 21 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 15 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria. 1 records from Triebesbach (Zeulenroda-Triebes). 22 records from AUM Fish Collection. 1 records from Berkel. 3 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 1 records from Mangfalltal. 24 records from Canadian Museum of Nature Fish Collection. 10 records from National System of Protected Areas in Poland - Animals. 25 records from Clare Biological Records Centre dataset. 1 records from Uferzone Wipper (Biesenrode). 1 records from Akita Prefectural Museum＋Actinopterygius Specimens of Akita Prefectural Museum. 118 records from NCSM Fishes Collection. 406 records from Swedish Board of Fisheries (Fiskeriverket) - National Register of Survey testfishing. 681 records from Natural History Museum (London) Collection Specimens. 1 records from Römertal (Steinpleis). 2 records from National Museum of Natural Science. 5 records from Atlantic Reference Centre (OBIS Canada). 1 records from Rund um das LUGY. 8 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 40509 records from Biological Records Centre - Database for the Atlas of Freshwater Fishes. 2 records from Wupperaue bei Kemna (Wuppertal). 1 records from Föhrenried (Fronreute und Baindt). 2 records from Colección Ictiológica del CENPAT-CONICET. 115 records from The Fish Collection. 1 records from Greater Manchester Ecology Unit - Distribution of Species of Conservation Interest in Greater Manchester. 200 records from naturgucker. 127 records from CUMV Fish Collection (Arctos). 117 records from North Carolina State Museum of Natural Sciences Fishes Collection. 1 records from Tiergarten Straubing. 1 records from Biosphärenpark Wienerwald - Pfaffstätten. 29957 records from United States Geological Survey Nonindigenous Aquatic Species Database. 8 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 1 records from Gronau - auf der Suche nach dem Neunauge. 2 records from Schussenaue bei Berg. 5 records from Staffordshire Ecological Record - SER Site-based Surveys. 1 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 1 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 167 records from New Mexico Biodiversity Collections Consortium database. 12 records from South Australian Museum Australia provider for OZCAM. 18 records from Fish specimens of Fisheries Research Laboratory Mie University. 2 records from Estonian Nature Observations Database. 107 records from Collection Ichthyologie - SNSD. 4189 records from Royal Netherlands Institute for Sea Research (NIOZ) - Kom Fyke Mokbaai. 10 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 5 records from KUBI Ichthyology Collection. 7 records from Fish tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 225 records from Museo Nacional de Ciencias Naturales, Madrid. Colección de Tejidos y ADN. 1 records from Varnhalt. 16 records from Tasmanian Museum and Art Gallery provider for OZCAM. 125 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 2 records from Pond Conservation - National Pond Monitoring Network collated pond survey data for Great Britain 1972 to 2007. 3 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 50 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 6 records from University of Ghent - Zoology Museum - Vertebratacollectie. 45760 records from NINA Vanndata fisk. 1 records from Priest Pot species list, Cumbria, Britain. 193 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 8 records from Staffordshire Ecological Record - SER Species-based Surveys. 187 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 3 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 1 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 46 records from CAS Ichthyology (ICH). 3 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 2 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 349 records from Monitoring data from the federal state Hesse (Germany). 1392 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 6 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 45 records from iNaturalist research-grade observations. 1 records from Marine Conservation Society - Seasearch Marine Surveys. 9793 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 25 records from Oregon State Ichthyology Collection. 1 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 8 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 2 records from Trekvis - Migratory fishes in the river Scheldt. 4 records from UCM Fish Collection (Arctos). 1 records from Artenvielfalt am Schlern. 1 records from Siegen/ Gymnasium Am Löhrtor. 6 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 26 records from UAIC Ichthyological Collection. 1 records from Im und um das Schulhaus. 870 records from VIS - Fishes in inland waters in Flanders, Belgium. 624 records from HMAP-History pf Marine Animal Populations (CoML). 1 records from Gieselbachtal Fulda-Harmerz. 1 records from Queensland Museum provider for OZCAM. 4 records from Western Australian Museum provider for OZCAM. 1 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 3 records from Fish Specimens. 5389 records from Atlas of Danish Fishes. 1 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 1 records from Tag der Artenvielfalt in der Stadt Luzern. 1 records from UAFMC Fish. 157 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 3361 records from Inventaire National du Patrimoine Naturel : Atlas des poissons d'eau douce de France métropolitaine (2011). 1 records from Gemeinde Sursee. 6 records from Image Database of Fishes in the Kanagawa Prefectural Museum of Natural History.
Keywords: GBIF; biodiversity; species occurrences